Application of modified cof membrane by crystal repair and cooperative structure reconfiguration in fuel cell
Patent Information
- Application Number
- CN202611207071.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-11
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2046-08-11
AI Technical Summary
[0005]有鉴于此,本发明提出一种晶体修复协同结构重构改性COF膜在燃料电池中的应用,旨在通过结构重构与缺陷修复,提高COF膜的结晶度及离子传导性能,解决现有技术中COF膜离子传导通道不连续、晶界阻抗高、氢氧根传导率受限的问题
[0017](1)宏观离子传导性能及器件性能提升效果:上述结构与传输路径的协同优化,使COF膜的氢氧根离子传导性能得到显著提升。在80 ℃、95%相对湿度条件下,经本发明处理后的COF膜,其OH-电导率可达120.16 mS cm-1以上,相较于未处理膜提升约115%,表明其性能已满足阴离子交换膜燃料电池的实际应用需求。进一步地,将该重构COF膜作为阴离子交换膜组装成燃料电池单电池,在相同测试条件下,其峰值功率密度较未处理膜提高30%以上,同时表现出更稳定的电流输出特性及更优异的长期运行稳定性。
Smart Images

Figure CN122716372B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of fuel cell technology, specifically to the application of a crystal repair synergistic structural reconstruction modified COF membrane in fuel cells. Background Technology
[0002] Anion exchange membrane fuel cells (AEMFCs) have outstanding advantages such as the use of non-precious metal catalysts, low operating costs, and environmental friendliness, and have become a research hotspot in the field of energy conversion. The hydroxide conductivity, water management characteristics, and mechanical stability of the anion exchange membrane directly determine the power generation output performance of the AEMFC. Covalent organic framework (COF) membranes have received widespread attention from the academic community as anion exchange membranes (AEMs) for fuel cells. COF membranes have a regular and ordered pore structure and a chemical microenvironment that is easy to functionalize, and have significant potential in ion conduction; however, at present, COF-based membrane materials still face several key technical bottlenecks: (1) low crystallinity and a large number of internal crystal defects; (2) high grain boundary impedance, which hinders the rapid migration of ions; (3) poor continuity of ion transport channels; and (4) difficulty in further improving hydroxide conductivity. The above problems together restrict the practical application of COF membranes in AEMFC systems.
[0003] Currently, research on improving the ion conductivity of COF membranes mainly focuses on monomer structure design, introduction of functional groups, and post-modification strategies, while research on methods for repairing crystal defects and reconstructing structures after membrane formation is relatively limited. Chinese patent application CN120888100A proposes a method for improving the crystallinity of flexible covalent organic framework membranes through solvothermal treatment. This method employs a two-step solution treatment process, using a mixed solution of acetic acid and acetonitrile at a temperature of 100 °C. This technical solution shows some positive effects in improving the crystallinity of the membrane material; however, its process steps are relatively complex, and the COF membrane structure synthesized in this patent lacks anion-conducting groups. This significant structural feature directly determines its lack of ion conductivity, making it unsuitable for use as anion exchange membranes in fuel cells.
[0004] Therefore, developing a COF membrane material with excellent ion conductivity suitable for fuel cell anion exchange membranes through a modification method of crystal repair and synergistic structural reconstruction has become an urgent technical problem to be solved in this field. Summary of the Invention
[0005] In view of this, this invention proposes an application of a crystal-repair synergistic structural reconstruction modified COF membrane in fuel cells. The aim is to improve the crystallinity and ion conductivity of the COF membrane through structural reconstruction and defect repair, addressing the problems of discontinuous ion conduction channels, high grain boundary impedance, and limited hydroxide ion conductivity in existing COF membranes. This method achieves intramembrane crystal structure reconstruction, defect repair, and pore ordering through trifluoroacetic acid-induced dynamic imine bond reversible recrystallization and methanol-assisted recrystallization. This improves the continuity of ion transport channels, reduces ion migration barriers, and thus significantly enhances the hydroxide ion conductivity of the COF membrane in fuel cells.
[0006] To achieve the above objectives, the present invention first provides an application of a crystal-repaired synergistic structure remodeling modified COF membrane in a fuel cell, wherein the fuel cell is an anion exchange membrane fuel cell; the application is to use the crystal-repaired synergistic structure remodeling modified COF membrane as the anion exchange membrane of the anion exchange membrane fuel cell.
[0007] The preparation steps of the crystal repair synergistic structure reconstruction modified COF membrane are as follows: the nascent COF membrane is completely immersed in methanol, heated, and then trifluoroacetic acid aqueous solution is added dropwise until the membrane color changes completely from the initial dark red to transparent orange-yellow. The dropwise addition is stopped, and the membrane is kept at the temperature to carry out the reconstruction reaction. After the reaction is completed, the membrane is taken out, washed, and dried to obtain the dark red crystal repair synergistic structure reconstruction modified COF membrane.
[0008] Its beneficial effects are as follows: trifluoroacetic acid acts as a dynamic covalent bond recombination promoter, inducing reversible exchange reactions of imine bonds; methanol acts as a recrystallization medium, dissolving oligomers within the pores and promoting crystal rearrangement and pore ordering. This invention utilizes the dissolving effect of methanol on oligomers and the reversible breaking and reconstructing effect of trifluoroacetic acid on imine bonds to repair internal crystal defects and fuse grain boundaries.
[0009] Compared to patent CN120888100A, this patent uses trifluoroacetic acid, a volatile strong acid with pKa=0.23, which provides higher proton activity. This allows the previously irreversible ketone-enamine structure in the COF synthesis of this patent to regain dynamic reversibility, while traditional acetic acid (pKa=4.76) cannot provide sufficient energy to break mismatched chemical bonds. Simultaneously, its -CF3 group has a strong electron-withdrawing effect, effectively promoting the delocalization of negative charges and improving ionic conductivity. Regarding the choice of solvent, the polar protic methanol, compared to the polar aprotic acetonitrile, can form competitive hydrogen bonds with TFA and protonate the COF oligomer, thus moderating the polymerization rate and maintaining reactivity.
[0010] Further, the heating temperature is 60~100℃; preferably, the heating temperature is 70~80℃.
[0011] Furthermore, the volume fraction of the trifluoroacetic acid aqueous solution is 95%, and the volume ratio of methanol to the trifluoroacetic acid aqueous solution is 1:1.
[0012] Furthermore, the temperature for the thermal insulation and reconstruction reaction is 60~100℃, and the time is 8min; preferably, the temperature for the thermal insulation and reconstruction reaction is 70~80℃.
[0013] The volume ratio of trifluoroacetic acid aqueous solution to methanol and the recrystallization temperature have a significant impact on the structural reconstruction effect of COF membranes. If the trifluoroacetic acid content is too high (e.g., the volume ratio of trifluoroacetic acid to methanol exceeds 3:1) or the recrystallization temperature is too high (e.g., exceeding 100 °C), the breaking effect of trifluoroacetic acid on imine bonds is too intense, the dynamic covalent bond exchange rate is too fast, resulting in damage to the integrity of the COF skeleton structure, stress concentration within the membrane, and ultimately, increased membrane brittleness and decreased flexibility. If the trifluoroacetic acid content is too low (e.g., the volume ratio of trifluoroacetic acid to methanol is less than 1:10) or the recrystallization temperature is too low (e.g., below 40 °C), the acid concentration is insufficient to effectively induce reversible breaking and recrystallization of imine bonds, the thermal energy of molecular chain segments is insufficient, making it difficult to achieve effective crystal reconstruction, and the improvement effect on crystallinity and ionic conductivity is not significant.
[0014] Furthermore, the washing process uses one or a combination of methanol and deionized water; the drying process is vacuum drying at a temperature of 60°C for 12 hours.
[0015] Further, the method for preparing the nascent COF membrane is as follows: First, an organic monomer containing an aldehyde group and an organic monomer containing an amino group are dissolved separately in a 95% (v / v) trifluoroacetic acid aqueous solution. Then, the two solutions are mixed evenly and poured into a quartz dish preheated to 70°C. Under the catalysis of trifluoroacetic acid, the organic monomer containing the aldehyde group and the organic monomer containing the amino group undergo a Schiff base condensation reaction to obtain an imine-bonded nascent COF membrane. Preferably, the organic monomer containing the aldehyde group in the preparation of the nascent COF membrane is trialdehyde phloroglucinol; the organic monomer containing the amino group includes one or more of ethidium bromide, methylphenidate bromide, and propidium iodide. The molar ratio of the organic monomer containing the aldehyde group to the organic monomer containing the amino group is 1:1.5; the molar amount of the organic monomer containing the aldehyde group to the volume ratio of the 95% (v / v) trifluoroacetic acid aqueous solution is 0.5 mmol: 0.5~1 mL.
[0016] In summary, this invention provides an application of a crystal-repaired, synergistically reconstructed COF membrane in a fuel cell. Compared with existing technologies, this invention has the following significant advantages:
[0017] (1) Improved macroscopic ion conduction performance and device performance: The synergistic optimization of the above structure and transport path significantly improves the hydroxide ion conduction performance of the COF membrane. Under conditions of 80 °C and 95% relative humidity, the COF membrane treated by this invention exhibits significantly improved OH- ion conduction performance. - The electrical conductivity can reach 120.16 mS / cm. -1 The above results represent an improvement of approximately 115% compared to the untreated membrane, indicating that its performance meets the practical application requirements of anion exchange membrane fuel cells. Furthermore, when this reconstructed COF membrane was used as an anion exchange membrane to assemble a single fuel cell, under the same test conditions, its peak power density was increased by more than 30% compared to the untreated membrane, while also exhibiting more stable current output characteristics and superior long-term operational stability.
[0018] (2) Crystal Defect Repair and Interface Reconstruction Effects: Addressing the common technical problems in existing covalent organic framework (COF) films, such as dense grain boundary defects, weak intergranular bonding, and a high proportion of amorphous regions in the pore structure, this invention utilizes trifluoroacetic acid to induce a reversible dynamic exchange reaction of imine bonds in the COF framework, leading to local bond rearrangement and interface reconstruction in the grain boundary regions. Simultaneously, combined with the selective dissolution effect of methanol on oligomers and disordered structures, effective fusion of intergranular interfaces and structural reconstruction of defect regions are achieved, thereby significantly reducing the internal defect density of the crystal. This process is not a simple solvent physical treatment but involves a structural reconstruction process involving dynamic covalent bonds, causing crystal rearrangement and preferential growth under the dual drive of thermodynamics and kinetics, achieving a transformation from amorphous regions to ordered crystalline structures throughout the entire membrane. X-ray diffraction (XRD) analysis results show that the diffraction peak intensity of the treated sample is significantly enhanced and the peak width is narrowed, indicating a significant increase in crystallinity. Meanwhile, the pore structure transforms from a state of local fracture or misalignment into a continuous and ordered channel, significantly reducing the tortuosity of the pores, thereby constructing a low-impedance ion transport network.
[0019] (3) Reduced ion migration barrier and optimized transport mechanism: Due to the significant reduction in grain boundary defects and the enhanced orderliness of the pore structure, the local barrier experienced by hydroxide ions during their migration within the membrane is significantly reduced. The ion transport path changes from the original discrete jumping mode blocked by grain boundaries to a continuous, low-barrier migration channel. Arrhenius correlation fitting results show that the conductivity of the COF membrane treated by this invention exhibits reduced temperature dependence, and the corresponding ion migration activation energy is significantly reduced, indicating that the energy barrier of the ion transport process is effectively weakened. It should be noted that this invention, through the synergistic effect of "structural reconstruction + pore rearrangement," transforms the ion transport mechanism from the traditional single diffusion path to a composite transport mode with the synergistic effect of the Grotthuss mechanism and the Vehicle mechanism, thereby further improving ion migration efficiency.
[0020] In summary, this invention not only achieves effective control of the microstructure of COF films, but also realizes cross-scale synergistic optimization from material structure optimization to device performance improvement, and has good prospects for engineering applications. Attached Figure Description
[0021] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on the provided drawings without creative effort.
[0022] Figure 1 A schematic diagram of the structure of TPEB-Br-COF after recrystallization.
[0023] Figure 2 Photograph of the TPEB-Br-COF thin film after recrystallization.
[0024] Figure 3 XRD comparison images of TPEB-Br-COF thin film before and after recrystallization.
[0025] Figure 4 Temperature impedance spectra of TPEB-OH-COF thin films at 100% RH before recrystallization.
[0026] Figure 5 Temperature impedance spectra of TPEB-OH-COF thin films after recrystallization at 100% RH.
[0027] Figure 6 Comparison of AEMFC power density curves at 60 °C before and after recrystallization of TPEB-OH-COF thin film.
[0028] Figure 7 A schematic diagram of the structure of TPDB-Br-COF after recrystallization.
[0029] Figure 8 Photograph of the thin film after recrystallization of TPDB-Br-COF.
[0030] Figure 9 XRD comparison images of TPDB-Br-COF thin film before and after recrystallization.
[0031] Figure 10 Temperature impedance spectra of TPDB-OH-COF thin films at 100% RH before recrystallization.
[0032] Figure 11 Temperature impedance spectra of TPDB-OH-COF thin films after recrystallization at 100% RH.
[0033] Figure 12 Comparison of AEMFC power density curves at 60 °C before and after recrystallization of TPDB-OH-COF thin film.
[0034] Figure 13 A schematic diagram of the structure of TPPI-I-COF after recrystallization.
[0035] Figure 14 Photograph of the TPPI-I-COF thin film after recrystallization.
[0036] Figure 15 XRD comparison images of TPPI-I-COF thin film before and after recrystallization.
[0037] Figure 16 Temperature impedance spectra of TPPI-OH-COF thin films at 100% RH before recrystallization.
[0038] Figure 17 Temperature impedance spectra of TPPI-OH-COF thin films after recrystallization at 100% RH.
[0039] Figure 18 AEMFC power density curves of TPPI-OH-COF thin film before and after recrystallization at 60 °C. Detailed Implementation
[0040] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0041] Example 1 S1, Preparation of COF film modified by crystal repair and synergistic structural reconstruction Weigh 11 mg of trialdehyde phloroglucinol (TP, 0.05 mmol) and 31 mg of ethidium bromide (EB, 0.075 mmol) into two separate 2 mL sample tubes. Add 1 mL of 95% trifluoroacetic acid (TFA) aqueous solution to each sample tube, which serves as both the solvent and catalyst. Seal the two sample tubes and ultrasonically disperse them for 5 min in an ultrasonic cleaner to ensure complete dissolution of the monomers. Then combine the solutions from the two tubes into a single sample tube and continue ultrasonic treatment for 2 min to ensure thorough and homogeneous mixing of the reaction precursors. Preheat the heating stage and ultra-flat-bottomed polished quartz dish to 70 °C. Then quickly pour the above mixed reaction solution into the preheated quartz dish and perform the Schiff base condensation film formation reaction in a fume hood. After 5 min of reaction, a uniform dark red film forms on the bottom of the quartz dish, which is the nascent TPEB-Br-COF film.
[0042] The nascent TPEB-Br-COF membrane was immersed in methanol and heated to 95 °C. Then, a 95% (v / v) trifluoroacetic acid (TFA) aqueous solution was added dropwise. The amount of trifluoroacetic acid added was determined to change the color of the membrane in the treatment solution from dark red to transparent orange-yellow (the volume ratio of trifluoroacetic acid to methanol in this example was measured to be 1:1). The reaction was maintained at 95 °C for 8 min. After reconstruction, the membrane was removed and repeatedly washed with methanol and deionized water until the waste liquid was clear and colorless. Then, it was placed in a vacuum drying oven at 60 °C for 12 h to obtain a dark red crystal repair synergistic structure reconstruction modified TPEB-Br-COF membrane.
[0043] A schematic diagram of the structure of the crystal repair synergistic remodeling modified TPEB-Br-COF membrane is shown below. Figure 1 See photos Figure 2 Macroscopic morphological observation of the TPEB-Br-COF films before and after recrystallization treatment revealed that the nascent TPEB-Br-COF film was a uniform dark red color with a smooth but slightly flexible surface. After recrystallization treatment, the film color changed to transparent orange-yellow, maintaining its complete macroscopic morphology, smooth and flat surface, and no obvious cracks or wrinkles. Furthermore, the film further flattened and grew, exhibiting good flexibility and allowing for bending and folding without breakage, indicating that the method of this invention improves crystallinity while maintaining the mechanical integrity of the film.
[0044] The crystal structure of the TPEB-Br-COF films before and after recrystallization was characterized using X-ray diffraction (Cu Kα radiation, λ = 1.5406 Å, 40 kV, 40 mA). The scanning range was 2θ = 2°–40°, and the scanning rate was 5° / min. The results are shown in [Figure number missing]. Figure 3As shown in the figure, the XRD pattern of the nascent TPEB-Br-COF film exhibits a low and wide (100) crystal plane characteristic diffraction peak in the low-angle region, while the interlayer (001) crystal plane characteristic diffraction peak is relatively high. This indicates that although a layered film structure has been formed, its crystallinity is low, and it is mainly an amorphous or semi-crystalline structure. After recrystallization treatment according to the present invention, the XRD pattern shows a sharp (100) crystal plane characteristic diffraction peak at 2θ ≈ 3.43°, and the peak width is significantly narrowed. This indicates that the crystallinity of the TPEB-Br-COF film is significantly improved after recrystallization treatment, the grain size is increased, and the long-range order of the crystal is significantly improved.
[0045] Temperature-dependent impedance spectroscopy (TIS) was performed on the TPEB-Br-COF membranes before and after recrystallization using a three-electrode AC impedance method. Before testing, both the nascent and recrystallized TPEB-Br-COF membrane samples were immersed in 1 M KOH solution for 24 h for ion exchange, followed by washing with deionized water until neutral, yielding the TPEB-OH-COF anion exchange membranes before and after recrystallization. The test conditions were: temperature 30 / 60 / 80 ℃, relative humidity 100%, frequency range 1 Hz~300000 Hz, AC amplitude 40 mV. The test results are shown below. Figure 4 and Figure 5 .
[0046] according to Figure 4 and Figure 5 Ionic conductivity (σ) is calculated using the formula σ = L / (R × A), where L is the distance between the two electrodes (cm), R is the membrane resistance (Ω), and A is the membrane cross-sectional area (cm²). 2 The effective area of the clamp is 1×1 cm. 2 The film thickness was measured to be 17 μm using a micrometer.
[0047] The ionic conductivity results are shown in Table 1. Under the conditions of 80 °C and 100% relative humidity, the OH- ion conductivity of the nascent TPEB-OH-COF membrane... - The conductivity is 55.88 mS·cm -1 After recrystallization treatment according to the present invention, the OH content of the TPEB-OH-COF membrane is... - The conductivity was significantly improved to 120.16 mS·cm -1 The improvement of approximately 115% compared to the untreated film indicates that the repair of grain boundary defects and the improvement of pore continuity effectively weaken the energy barrier in the ion transport process.
[0048] Table 1. Test data on ionic conductivity of TPEB-OH-COF
[0049] S2 fuel cell fabrication The recrystallized TPEB-Br-COF membrane sample was immersed in 1 M KOH solution for 24 h for ion exchange to obtain the TPEB-OH-COF membrane. This membrane was then used as the anion exchange membrane to assemble a single fuel cell. The fuel cell's membrane electrode assembly consists of a catalyst layer with platinum-ruthenium carbon (Johnson Matthey, Japan, 60wt% total metal loading, Pt:Ru=1:1) supported on the anode, a catalyst layer with platinum carbon (TANAKA, Japan, 57wt% platinum loading) supported on the cathode, and an anion exchange membrane sandwiched between the anode and cathode. A gas diffusion layer (GDL), using Freudenberg carbon paper H23C2, is disposed on the side of the anode away from the anion exchange membrane and the side of the cathode away from the anion exchange membrane, respectively. Bipolar plates, using graphite composite material, are disposed on the side of the gas diffusion layer on the anode side away from the anode and the side of the gas diffusion layer on the cathode side away from the cathode, respectively. End plates and conductive plates are battery fixing components disposed on the outside of the anode and cathode bipolar plates. (The entire system, including the clamps, is SunlaiteTE 201.) 100W).
[0050] The performance of the prepared fuel cell was tested under the following conditions: cathode loading of 0.4 mg Pt / cm³. 2 The anode loading was 0.4 mg PGM / cm³. 2 The battery temperature is 60 ℃, and the anode fuel is humidified hydrogen gas (flow rate 500 mL·min). -1 The cathode is humidified oxygen (flow rate 300 mL / min). -1 The back pressure was 0.2 MPa for all cells. The polarization and power density curves of the cells were recorded using an electrochemical workstation. The test results are shown below. Figure 6 The results showed that the peak power density of the single cell assembled using the nascent TPEB-OH-COF membrane was only 895.8 mW·cm⁻¹. -2 The single cell assembled using the TPEB-OH-COF membrane after recrystallization treatment according to this invention achieved a peak power density of 1228.5 mW·cm⁻¹. -2 The yield was improved by approximately 37.1% compared to the untreated membrane. Furthermore, the battery assembled with the recrystallized membrane exhibited more stable voltage output characteristics in the constant current discharge test, indicating a significant improvement in its long-term operational stability.
[0051] Example 2 S1, Preparation of COF film modified by crystal repair and synergistic structural reconstruction Weigh 11 mg of trialdehyde phloroglucinol (TP, 0.05 mmol) and 30 mg of methylphenidate bromide (DB, 0.075 mmol) into two separate 2 mL sample tubes. Add 1 mL of 95% trifluoroacetic acid (TFA) aqueous solution to each sample tube, which serves as both the solvent and catalyst. Seal the two sample tubes and ultrasonically disperse them for 5 min in an ultrasonic cleaner to ensure complete dissolution of the monomers. Then combine the solutions from the two tubes into a single sample tube and continue ultrasonic treatment for 2 min to ensure thorough and homogeneous mixing of the reaction precursors. Preheat the heating stage and ultra-flat-bottomed polished quartz dish to 70 °C. Then quickly pour the above mixed reaction solution into the preheated quartz dish and perform the Schiff base condensation film formation reaction in a fume hood. After 5 min of reaction, a uniform dark red film forms on the bottom of the quartz dish, which is the nascent TPDB-Br-COF film.
[0052] The nascent TPDB-Br-COF membrane was immersed in methanol and heated to 95 °C. Then, a 95% (v / v) trifluoroacetic acid (TFA) aqueous solution was added dropwise. The amount of trifluoroacetic acid added was determined to change the color of the membrane in the treatment solution from dark red to transparent orange-yellow (the volume ratio of trifluoroacetic acid to methanol in this example was determined to be 1:1). The reaction was maintained at 95 °C for 8 min. After reconstruction, the membrane was removed and repeatedly washed with methanol and deionized water until the waste liquid was clear and colorless. Then, it was placed in a vacuum drying oven at 60 °C for 12 h to obtain a dark red crystal repair synergistic structure reconstruction modified TPDB-Br-COF membrane.
[0053] A schematic diagram of the structure of the crystal repair synergistic reconstructed modified TPDB-Br-COF membrane is shown below. Figure 7 See photos Figure 8 .
[0054] The crystal structure of the TPDB-Br-COF film before and after recrystallization was characterized using X-ray diffraction (Cu Kα radiation, λ = 1.5406 Å, 40 kV, 40 mA). The scanning range was 2θ = 2°–40°, and the scanning rate was 5° / min. The results are shown in [Figure number missing]. Figure 9As shown in the figure, the diffraction pattern of the nascent TPDB-Br-COF film exhibits broad, diffuse peaks in the low-angle region, without any obvious Bragg diffraction peaks. After recrystallization treatment according to the present invention, the XRD pattern of the TPDB-Br-COF film shows significant (100) crystal plane characteristic diffraction peaks at 2θ≈3.46°, and the peak width is significantly narrowed, indicating that the crystallinity of the TPDB-Br-COF film is significantly improved after recrystallization treatment. Example 2 uses the same recrystallization treatment conditions as Example 1, and successfully realizes the structural transformation of the bromomethylphenidate-based COF system from a low-crystallinity state to a high-crystallinity ordered state, further verifying that the method of the present invention has good universality for different COF systems.
[0055] Temperature-dependent impedance spectroscopy (TIS) was performed on the TPDB-Br-COF membranes before and after recrystallization using a three-electrode method. Before testing, both the nascent and recrystallized TPDB-Br-COF membrane samples were immersed in 1 M KOH solution for 24 h for ion exchange, followed by washing with deionized water until neutral, yielding the TPDB-OH-COF anion exchange membranes before and after recrystallization. The test conditions were: temperature 30 / 60 / 80 ℃, relative humidity 100%, frequency range 1 Hz~300000 Hz, AC amplitude 40 mV. The test results are shown below. Figure 10 and Figure 11 .
[0056] according to Figure 10 and Figure 11 Ionic conductivity is calculated using the formula σ = L / (R × A), where L is the distance between the two electrodes (cm), R is the membrane resistance (Ω), and A is the membrane cross-sectional area (cm²). 2 The effective area of the clamp is 1×1 cm. 2 The film thickness was measured to be 30 μm using a micrometer.
[0057] The ionic conductivity results are shown in Table 2. Under the conditions of 80 °C and 100% relative humidity, the OH- ion conductivity of the nascent TPDB-OH-COF membrane... - The conductivity is 8.04 mS·cm -1 After recrystallization treatment according to the present invention, the OH content of the TPDB-OH-COF membrane is... - The conductivity was significantly improved to 99.70 mS·cm -1 The significant improvement compared to the untreated film indicates that the repair of grain boundary defects and the improvement of pore continuity effectively weaken the energy barrier in the ion transport process.
[0058] Table 2. Test data on ionic conductivity of TPDB-OH-COF
[0059] S2 fuel cell fabrication The recrystallized TPDB-Br-COF membrane sample was immersed in 1 M KOH solution for 24 h for ion exchange to obtain TPDB-OH-COF membrane. It was used as an anion exchange membrane to assemble a fuel cell single cell. The specific fuel cell structure was the same as in Example 1.
[0060] The performance of the prepared fuel cell was tested under the following conditions: cathode loading of 0.4 mg Pt / cm³. 2 The anode loading was 0.4 mg PGM / cm³. 2 The battery temperature is 60 ℃, and the anode fuel is humidified hydrogen gas (flow rate 500 mL·min). -1 The cathode is humidified oxygen (flow rate 300 mL·min). -1 The back pressure was 0.2 MPa for all cells. Polarization and power density curves were recorded using an electrochemical workstation. Results are shown below. Figure 12 The results showed that the peak power density of the single cell assembled using the nascent TPDB-OH-COF membrane was only 745.3 mW·cm⁻¹. -2 The single cell assembled using the recrystallized TPDB-OH-COF membrane of this invention achieved a peak power density of 1023.5 mW·cm⁻¹. -2 It improves by approximately 37.3% compared to the untreated membrane.
[0061] Example 3 S1, Preparation of COF film modified by crystal repair and synergistic structural reconstruction Weigh 11 mg of trialdehyde phloroglucinol (TP, 0.05 mmol) and 53 mg of propidium iodide (PI, 0.075 mmol) into two separate 2 mL sample tubes. Add 0.5 mL of 95% trifluoroacetic acid (TFA) aqueous solution to each sample tube, which serves as both the solvent and catalyst. Seal the two sample tubes and ultrasonically disperse them for 5 min in an ultrasonic cleaner to ensure complete dissolution of the monomers. Then combine the solutions from the two tubes into a single sample tube and continue ultrasonic treatment for 2 min to ensure thorough and homogeneous mixing of the reaction precursors. Preheat the heating stage and ultra-flat-bottomed polished quartz dish to 70 °C. Then quickly pour the above mixed reaction solution into the preheated quartz dish and perform the Schiff base condensation film formation reaction in a fume hood. After 5 min of reaction, a uniform dark red film forms on the bottom of the quartz dish, which is the nascent TPPI-I-COF film.
[0062] The nascent TPPI-I-COF membrane was immersed in methanol and heated to 60 °C. Then, a 95% (v / v) trifluoroacetic acid (TFA) aqueous solution was added dropwise. The amount of trifluoroacetic acid added was determined to change the color of the membrane in the treatment solution from dark red to transparent orange-yellow (the volume ratio of trifluoroacetic acid to methanol in this example was determined to be 1:1). The reaction was maintained at 60 °C for 8 min. After reconstruction, the membrane was removed and repeatedly washed with methanol until the waste liquid was clear and colorless. Then, it was placed in a vacuum drying oven at 60 °C for 12 h to obtain a dark red crystal repair synergistic structure reconstruction modified TPPI-I-COF membrane.
[0063] A schematic diagram of the structure of the crystal repair synergistic structure reconstructed and modified TPPI-I-COF membrane is shown below. Figure 13 See photos Figure 14 The structure is thin, uniform, and intact.
[0064] The crystal structure of the TPDB-Br-COF film before and after recrystallization was characterized using X-ray diffraction (Cu Kα radiation, λ = 1.5406 Å, 40 kV, 40 mA). The scanning range was 2θ = 2°–40°, and the scanning rate was 5 ° / min. The results are shown in [Figure number missing]. Figure 15 Unlike the relatively rigid COF systems in Examples 1 and 2, the long-chain COF used in this example exhibits higher molecular chain flexibility, leading to a significant tendency for random coiling of molecular chain segments under conventional film-forming conditions. This results in a weaker thermodynamic driving force for the ordered crystal arrangement, making it more difficult to form sharp crystal diffraction peaks. XRD results show that the diffraction pattern of the nascent TPPI-I-COF film only presents a broad, diffuse peak, with no obvious Bragg diffraction peak observed, indicating that it is essentially in an amorphous state. After recrystallization treatment according to this invention, the XRD pattern of the long-chain COF film shows obvious (100) crystal plane characteristic diffraction peaks in the low-angle region, while new diffraction peaks corresponding to the (200) crystal plane appear in the high-angle region, with significantly narrowed peak widths. The appearance of the (200) crystal plane diffraction peak indicates that the recrystallization treatment method of this invention not only improves the crystallinity of the COF material but also induces crystal growth along specific crystal plane orientations, further confirming the multi-dimensional improvement effect of crystal reconstruction on crystal order. This indicates that even for long-chain flexible COF systems that are difficult to crystallize, the present invention can still effectively induce the ordered arrangement of molecular chain segments and crystal reconstruction at a lower recrystallization temperature, significantly improving the crystallinity of the film material and achieving preferred orientation growth of specific crystal planes.
[0065] Temperature-dependent impedance spectroscopy (TIS) was performed on the TPPI-I-COF membranes before and after recrystallization using a three-electrode AC impedance method. Before testing, both the nascent and recrystallized TPPI-I-COF membrane samples were immersed in 1 M KOH solution for 24 h for ion exchange, followed by washing with deionized water until neutral, yielding the TPPI-OH-COF anion exchange membranes before and after recrystallization. The test conditions were: temperature 30 / 60 / 80 ℃, relative humidity 100%, frequency range 1 Hz~300000 Hz, AC amplitude 40 mV. The test results are shown below. Figure 16 and Figure 17 .
[0066] according to Figure 16 and Figure 17 Ionic conductivity (σ) is calculated using the formula σ = L / (R × A), where L is the distance between the two electrodes (cm), R is the membrane resistance (Ω), and A is the membrane cross-sectional area (cm²). 2 The effective area of the clamp is 1×1 cm. 2 The film thickness was measured to be 9 μm using a micrometer.
[0067] The ionic conductivity results are shown in Table 3. Under the conditions of 80 °C and 100% relative humidity, the OH- ions of the nascent TPPI-OH-COF membrane... - The conductivity is 277.16 mS·cm -1 After recrystallization treatment according to the present invention, the OH groups of the TPPI-OH-COF membrane are... - The conductivity was significantly improved to 480.71 mS·cm -1 The significant improvement compared to the untreated film indicates that the repair of grain boundary defects and the improvement of pore continuity effectively weaken the energy barrier in the ion transport process.
[0068] Table 3. Test data on ionic conductivity of TPPI-OH-COF
[0069] The recrystallized TPPI-I-COF membrane sample was immersed in 1 M KOH solution for 24 h for ion exchange to obtain TPPI-OH-COF membrane. It was used as an anion exchange membrane to assemble a fuel cell single cell. The specific fuel cell structure was the same as in Example 1.
[0070] The performance of the prepared fuel cell was tested under the following conditions: cathode loading of 0.4 mg Pt / cm³. 2 The anode loading was 0.4 mg PGM / cm³. 2 The battery temperature is 60 ℃, and the anode fuel is humidified hydrogen gas (flow rate 500 mL·min). -1The cathode is humidified oxygen (flow rate 300 mL·min). -1 The back pressure was 0.2 MPa for all cells. Polarization and power density curves were recorded using an electrochemical workstation. Results are shown below. Figure 18 The results showed that the peak power density of the single cell assembled using the nascent TPPI-OH-COF membrane was only 1177.72 mW·cm⁻¹. -2 The single cell assembled using the TPPI-OH-COF membrane after recrystallization treatment according to this invention achieved a peak power density of 1483.03 mW·cm⁻¹. -2 It has good performance.
[0071] Various modifications to these embodiments will be readily apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the invention. Therefore, the invention is not to be limited to the embodiments shown herein, but is to be accorded the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. The application of a crystal-repaired, synergistically reconstructed COF membrane in a fuel cell, characterized in that, The fuel cell is an anion exchange membrane fuel cell; the application is to use a crystal repair synergistic structure reconstruction modified COF membrane as the anion exchange membrane of the anion exchange membrane fuel cell; The preparation steps of the crystal repair synergistic structure reconstruction modified COF membrane are as follows: The nascent COF membrane is completely immersed in methanol, heated, and then trifluoroacetic acid aqueous solution is added dropwise until the membrane color changes completely from the initial dark red to transparent orange-yellow. The dropwise addition is stopped, and the membrane is kept at this temperature for the reconstruction reaction. After the reaction is complete, the membrane is removed, washed, and dried to obtain the dark red crystal repair synergistic structure reconstruction modified COF membrane. The heating temperature is 60~100℃; the volume fraction of the trifluoroacetic acid aqueous solution is 95%, and the volume ratio of methanol to trifluoroacetic acid aqueous solution is 1:1; the temperature for the reconstruction reaction is 60~100℃, and the time is 8 min. The method for preparing the nascent COF membrane is as follows: First, an organic monomer containing an aldehyde group and an organic monomer containing an amino group are dissolved in a 95% trifluoroacetic acid aqueous solution. Then, the two solutions are mixed evenly and poured into a quartz dish preheated to 70°C. Under the catalysis of trifluoroacetic acid, the organic monomer containing an aldehyde group and the organic monomer containing an amino group undergo a Schiff base condensation reaction to obtain the nascent COF membrane. The organic monomer containing an aldehyde group is trialdehyde phloroglucinol; The amino-containing organic monomers include one or more of ethidine bromide, methylphenidate bromide, and propidium iodide.
2. The application according to claim 1, characterized in that, The washing process uses methanol or deionized water, or a combination thereof; the drying process is vacuum drying at 60°C for 12 hours.
3. The application according to claim 1, characterized in that, The molar ratio of the aldehyde-containing organic monomer to the amino-containing organic monomer is 1:1.5; the molar amount of the aldehyde-containing organic monomer to the volume ratio of the 95% trifluoroacetic acid aqueous solution is 0.5 mmol: 0.5~1 mL.
Citation Information
Patent Citations
Method for improving crystallinity of flexible covalent organic framework film through solvent heat treatment
CN120888100A
